Deep carbon dioxide flows substantially contributes to soil-atmosphere carbon flux from Robinia pseudoacacia forests - Wanglin Hao; Binbin Li; Bin Xia; Mingxiang Xu (Ecological Indicators, 2022)
Alterations in land use and vegetation cover cause CO2 transfer not only to the soil surface but also across soil profiles. To explore the vertical diffusion characteristics of CO2 in deep soil profiles and their driving factors, we calculated CO2 flux and measured environmental factors in sections situated from 0 to 200 cm in Robinia pseudoacacia forests (Loess Hilly Region, China). The results found that (1) Deep soils (>80 cm) exhibited a stable contribution to the soil-atomosphere CO2 flux, ranging from 21.81% to 24.42%. (2) The total CO2 storage within deep layers accounted for 55.03–79.98% of the total storage in the layer at 0–200 cm. The stable storage of CO2 at deep layers helped suppress the mineralization of organic carbon in deep soil; (3) Soil temperature, moisture, CO2 concentration, aerated porosity, SOC content, bulk density, total porosity, root density, microbial biomass carbon (MBC), pH, and profile depth explained 86.0% and 89.1% of the variance in CO2 flux at shallow and deep layers, respectively. Soil moisture was the key limiting factor for vertical differentiation of CO2 fluxes in deep and shallow layers. The sensitivity of temperature and aerated porosity on CO2 flux increased with soil depth increasing. While the soil microbial biomass carbon had a weaker effect on CO2 flux both in the deep and shallow layers. Root stimulation was more likely to induce CO2 emission in deep layers. However, increase of pH was more conducive to CO2 fixation and flux reduction in deep layers. Our results help to further clarify the mechanisms of carbon emission in deep soil carbon pools, and provide a theoretical basis for scientific evaluation of soil carbon emissions.